Near-far field multipath spatial-temporal localisation - Venieris,E; Manikas,A (Institute of Electrical and Electronics Engineers, 2017)
In this paper, a passive array processing algorithm isproposed for localising the near-far field multipaths of the desiredsignal in the presence of co-channel interference. By expressingthe unknown path delay as a function of the path’s range,the proposed spatiotemporal localisation algorithm estimates thelocations of all the multipath reflectors of the desired signalsource using a subspace-type cost function. The performance ofthe proposed algorithm is evaluated through computer simulationstudies.